STATISTICAL ACCOUNTING PROCEDURES. - Crawford, James R. (The Accounting Review, 1944)
The installation of efficient statistical accounting procedures in an aircraft factory poses problems for the solution of which a consideration of what is being done in other lines of business is of primary value. There are certain fundamental theories which apply to all classes of industries. The aircraft industry is only a specific case in the application of these fundamentals. The problems of the aircraft industry are not unique, they are merely variations of the production problems found in many other industries. The aircraft industry is best represented by a combination of the automobile business and a job shop business. The aircraft industry manufactures a small quantity of a large variety of parts. In addition to this small quantity production, the aircraft industry must be ready, at a moment's notice, to change the design of the product for tactical reasons. Another item that affects the aircraft industry more than any other is the weight of the product. Parts are often made at great expense just to reduce weight. It is thus readily apparent that cost methods of different manufacturers require the application of different manufacturing accounting techniques.